Pengaruh Outsourcing Terhadap Keunggulan Kompetitif Perusahaan - Puspadewi, Gladys Trias; Insani, Gema Mutiara; Hasnakusumah, Raisha Tiara; Rumbung, Krispinus Kevin (Media Hukum Indonesia (MHI), 2024)
Outsourcing has become a common business strategy used by companies to improve operational efficiency and efficiency. However, the impact of outsourcing on the competitive advantage of companies remains a controversial topic.Outsourcing is a way in which companies hand over part of their business functions or processes to external parties or other companies that are more specialized in the field. The objective of outsourcing is to increase efficiency, reduce operating costs, and enable companies to focus on core competencies that are being experienced. The study aims to analyze the influence of outsourcing on the competitive advantage of companies. The study uses the methodology of literature review by analyzing various scientific sources, such as academic journals, books, and research reports. Research results show that outsourcing can have a positive and a negative impact on the competitive advantage of companies. The influence of outsourcing on the competitive advantage of a company depends on a variety of factors, such as the type of activity that is outsourced, the choice of the company to outsource, and the company's ability to manage the relationship. Therefore, companies need to carefully consider all these factors before deciding to do outsourcing.